Vol 1 Maret 2023 MEMBANGUN LITERASI KEUANGAN DAN INVESTASI SYARI'AH: PEMBERDAYAAN UMKM MELALUI BANK WAKAF MIKRO - Masruri Masruri (IKHTIYAR JURNAL EKONOMI SYARI'AH, 2023)
The synergy of the Micro Waqf Bank Program with Qardhul Hasan is a debt that can be given either in the form of money or in the form of borrowed goods, such as cars, laptops, motorbikes or others, with the condition that the loan recipient must return the goods to the owner in their original condition without any part. taken or without any addition to the item. The end and main goal of the Micro Waqf Bank Program with the al Qordhul Hasan contract is the prosperity of the community as a result of the chain effect arising from the procurement of infaq and shadaqah funds for muzakki, based on the nature and high sense of concern for others.Thus, the Qardhul Hasan contract in the Micro Waqf Bank Program is carried out on the basis of social, humanitarian and mutual welfare by helping to provide capital for businesses. The implementation of the Qardhul hasan contract in Islamic financial institutions can be an option for someone who needs loan funds. If the recipient of the debt wants to give charity, it is not determined by the debtor, but on the consciousness of oneself.